Affective and Cognitive Correlates of Reading Comprehension: A Structural Analysis - Alfiani, Elsa; Anggia, Helta; Harpain, Harpain; Yanu Dharmawan, Yanuarius; Magdalena Sidabalok, Dameria; Lakatos, Kristóf (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigated the impact of reading motivation, dictation, vocabulary, and socioeconomic status on students’ reading comprehension. A quantitative research methodology was employed, with data collected over four sessions involving tenth-grade students from SMA Yadika Bandar Lampung. The data were gathered through multiple - choice tests, questionnaires, and dictation assessments. The results demonstrated a strong positive correlation between decoding skills and vocabulary in relation to reading comprehension. Statistically significant p-values of 0.000 were found for the relationships between decoding and English reading comprehension (DEC->ERC), decoding and vocabulary (DEC-> VOC), vocabulary and reading comprehension (VOC - >ERC), as well as the combined effects of dictation and vocabulary on English reading comprehension (DEC - >VOC - >ERC). The findings highlight that both dictation skills and vocabulary development play a crucial role in enhancing reading comprehension. In contrast, the study found no significant relationship reading motivation or socioeconomic status and reading comprehension. The correlations betw een extrinsic motivation and English reading comprehension (EM->ERC), intrinsic motivation and English reading comprehension (IM->ERC), and family income and English reading comprehension (INC->ERC) were not statistically significant. These results suggest that while dictation and vocabulary skills are essential for reading comprehension, factors such as reading motivation and socioeconomic status did not exert a significant influence in the study. The findings underscore the importance of focusing on vocabulary and dictation skills to improve students’ reading comprehension, suggesting that targeted educational interventions in these areas could lead to enhanced academic performance for all students. HIGHLIGHTS: Impact of Decoding Skills and Vocabulary on Reading Comprehension: The study shows a strong link between students' decoding skills and vocabulary knowledge, which both greatly improve reading comprehension. Decoding directly helps build vocabulary, which then supports reading comprehension. Vocabulary alone accounts for 75.2% of the differences in reading comprehension, emphasizing its key role. Limited Influence of Socioeconomic and Motivational Factors: Unlike some past studies, this research found that socioeconomic status, intrinsic motivation, and extrinsic motivation have little to no impact on reading comprehension. This suggests that cognitive skills, like decoding and vocabulary, are more important for students' reading abilities than socioeconomic or motivational factors. Educational Implications for Curriculum Development: The findings highlight the need to focus on cognitive skills, especially vocabulary and decoding, in reading instruction. Prioritizing these core skills can help educational programs improve students' reading comprehension and close literacy gaps across diverse groups.